2012
DOI: 10.5433/1679-0359.2012v33supl1p2905
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade física e produção do maracujá amarelo em solo com biofertilizante irrigado com águas salinas

Abstract: ResumoA cultura do maracujazeiro apresentou nos últimos anos expansão da área cultivada, motivada, principalmente, pelo aumento do consumo interno da fruta in natura e pelo suco processado. Atualmente o Brasil é o maior produtor e consumidor mundial do maracujá amarelo (Passiflora edulis Sims. f. flavicarpa Deg.), no entanto, a produção nacional não supriu a demanda do mercado agroindustrial. O objetivo deste trabalho foi avaliar os efeitos de diferentes condutividades elétricas da água de irrigação (CEai), as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 16 publications
3
19
0
8
Order By: Relevance
“…Such restriction caused by salinity can be related to the osmotic effect resulting from salinity, limiting water availability and, consequently, gas exchange, particularly in photosynthesis, as observed in other studies (DIAS et al, 2012;BRITO et al, 2012). In addition, ionic effects might have played a role, since plants had been under irrigation with saline water for 30 days in a relatively small volume of substrate; this corroborates with the findings of Hussain et al (2015), who related low photosynthesis values in citrus leaves to a low detoxification capacity, leading to the accumulation of ions in the cell vacuole.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Such restriction caused by salinity can be related to the osmotic effect resulting from salinity, limiting water availability and, consequently, gas exchange, particularly in photosynthesis, as observed in other studies (DIAS et al, 2012;BRITO et al, 2012). In addition, ionic effects might have played a role, since plants had been under irrigation with saline water for 30 days in a relatively small volume of substrate; this corroborates with the findings of Hussain et al (2015), who related low photosynthesis values in citrus leaves to a low detoxification capacity, leading to the accumulation of ions in the cell vacuole.…”
Section: Resultsmentioning
confidence: 76%
“…However, although irrigation can reduce the climatic risk of drought and losses of citrus orchards in the Northeastern region, it must be highlighted that the water used for irrigation, which is usually obtained from wells, has relatively high salt concentrations, which can influence the growth, development and yield of the salt-sensitive citrus plants (MAAS, 1993;MEDEIROS et al, 2003;LEVY;SYVERTSEN, 2004;DIAS et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Passion fruit irrigation with saline water has been investigated in several studies (DIAS et al, 2012;FREIRE et al, 2012;VIANA et al, 2012). In general, these studies have shown that salinity reduces the growth of branches and several other growth components, besides compromising some chemical characteristics of the fruits when irrigation is carried out with waters of moderate to high salinity.…”
Section: Introductionmentioning
confidence: 99%
“…, induced by the competition with Na + , or even of NO 3 -due to the high concentration of Cl -in the environment, which damages the functions of the enzymatic systems and impedes protein synthesis (APSE; BLUMWALD, 2007;DIAS et al, 2012b).…”
Section: +mentioning
confidence: 99%